2021
DOI: 10.3390/agronomy11112141
|View full text |Cite
|
Sign up to set email alerts
|

Typology of Consumers According to the Declared Consumption of Food Products and Non-Alcoholic Beverages. Polish and Slovakian Case Studies

Abstract: The aim of the paper is to create a typology of consumers based on the consumption of food products and non-alcoholic beverages for two countries. The research was conducted among non-randomized respondents representing 900 Polish and 300 Slovakian households. The Polish part of the study was carried out in the Silesian and Mazovian provinces. The Slovakian part of the study was carried out in the whole country. To identify four groups of consumers, the paper used the clustering of objects method, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Obesity rates in Slovakia are on the rise and higher than the EU average. Low fruit and vegetable intake and insufficient physical activity of 30–40% of Slovak inhabitants represent another salient problem in health management (Maciejewski et al, 2021 ; World Obesity Federation, 2021 ; OECD, 2023 ). In addition, the health status of the Slovak population lags behind the EU average (OECD, 2019 , 2021 , 2023 ) while about half of the deaths in Slovakia can be associated with behavioral risk factors, including dietary risks and low levels of physical activity, which is higher than the EU average of two in five deaths (Maciejewski et al, 2021 ; OECD, 2021 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity rates in Slovakia are on the rise and higher than the EU average. Low fruit and vegetable intake and insufficient physical activity of 30–40% of Slovak inhabitants represent another salient problem in health management (Maciejewski et al, 2021 ; World Obesity Federation, 2021 ; OECD, 2023 ). In addition, the health status of the Slovak population lags behind the EU average (OECD, 2019 , 2021 , 2023 ) while about half of the deaths in Slovakia can be associated with behavioral risk factors, including dietary risks and low levels of physical activity, which is higher than the EU average of two in five deaths (Maciejewski et al, 2021 ; OECD, 2021 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low fruit and vegetable intake and insufficient physical activity of 30–40% of Slovak inhabitants represent another salient problem in health management (Maciejewski et al, 2021 ; World Obesity Federation, 2021 ; OECD, 2023 ). In addition, the health status of the Slovak population lags behind the EU average (OECD, 2019 , 2021 , 2023 ) while about half of the deaths in Slovakia can be associated with behavioral risk factors, including dietary risks and low levels of physical activity, which is higher than the EU average of two in five deaths (Maciejewski et al, 2021 ; OECD, 2021 , 2023 ). Thus, it is crucial to identify the behavioral, social, and cultural factors that influence human behavior to provide more evidence-based, effective, and people-centered services and policies for effective health change (WHO, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it requires a target number of extracted groups of individuals, and this number is not predetermined. To obtain this information, one should first use hierarchical cluster analysis [39]. Therefore, the applied two-stage process enables better, more substantive results to be achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Attitudes towards sustainable development and sustainable behavior of young individuals from Generations Z (18-24 years old) and Y (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) were studied by Zalega [2]. His analyses showed that young people often engage in pro-environmental behavior as part of sustainable behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Desde el punto de vista metodológico, la investigación busca clasificar grupos de acuerdo con características como: comportamientos de compra y consumo (Huseynov y Özkan, 2019;Maciejewski et al, 2021), estilos de vida (Schnettler et al, 2012;Tian y Boucher, 2021), e intereses (Hallem, Ben Arfi, y Teulon, 2020), metodología que constituye una manera de describir la homogeneidad en los subgrupos contenidos en una población, a fin de clasificar a los elementos de la población de acuerdo con la relación natural existente (Suárez, 1999).…”
Section: Introductionunclassified